The management success of the invasive late goldenrod (Solidago gigantea Aiton.) in a nature conservation area is strongly related to site, control measures and environmental factors - Rea Maria Hall; Bernhard Urban; Hans-Peter Kaul (PeerJ, 2022)
The late goldenrod (Soldiago gigantea Aiton; Asteraceae) is one of the most abundant invasive species in various types of habitats. Its long-creeping plagiotropic rhizomes enable the plant to build up dense, monospecific stands within a short time. Particularly in nature conservation areas, the invasion of goldenrod can cause severe disruptions in the naturally occuring mutualims between plants, insects and higher trophic levels, subsequently impeding the achievement of nature conservation goals. As management options of goldenrod in nature conservation areas are limited, this three-year study aimed to test the effectiveness of three management treatments (two-time mowing, triticale cultivation, and reverse rotary cutting) on four different sites in the Austrian Donau-Auen National Park. The number and height of goldenrod shoots were recorded three times a year on twelve permanent trial plots on each site to test for the effectiveness of the treatments. In addition, vegetation surveys were performed to observe the recovery potential of native plant species. Even though the three-years mowing and the triticale cultivation reduced goldenrod by 95.6% and 97.2% resp., we could find no relation between the effectiveness of the treatment and the intensity of disturbance created by the control option. On the contrary, with a reduction of only 5.4% in goldenrod density the most intensive treatment, the rotary cutting, showed the lowest efficiency. The highest positive effect on the re-establishment of native plant species was recorded with two mowing events per year. Even though the study revealed that certain management options have the potential to effectively reduce goldenrod and to simultaneously increase the establishment success of native species, results can only be seen as so-called snapshots. For example, as shown on site EJW one unforeseeable wild boar digging event transformed a 84.5% reduction into a 4.7% increase in goldenrod density. Therefore, a proper and regular monitoring is essential to be able to react to the effects of unpredictable events that can have severe impact on vegetation dynamics.